Gambaran Sisa Makanan Biasa Yang Disajikan Diberi Garnis Dan Tidak Diberi Garnis Diruang Vip Rsud Undata Provinsi Sulawesi Tengah: Description Of Ordinary Left Over Served With Garnished And Ungarnised In VIP Ward Of Undata Hospital Of Central Sulawesi - Putu Candriasih; Hermin Austeria; Made Ayu Puspitawati (Poltekkes Kemenkes Palu, 2021)
The hospital is one of the health service industries which initially only carried out activities and recovery. However, with the development of science and technology, hospitals tooIncreasing efforts to improve service quality. The purpose of This research is to see the overview of the usual leftovers that are served given garnish and not given garnish in the VIP room of Undata Hospital Palu, Central Sulawesi Province. This research method is descriptive. The results obtained were 6 respondents for the food given Garnish, of the 6 respondents there is no leftover.While 6 respondents for food that was not given garnish, out of 6 respondents only 1 respondent whose were not leftover and 5 respondents had leftovers (staple food, animal side dishes, vegetable side dishes, vegetables).